2021
DOI: 10.1177/15598276211006342
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Relevancy of Culinary and Nutritional Medicine Interventions: A Scoping Review

Abstract: Background. Taking into account the disproportionate impacts of disease burden from chronic conditions by racial and ethnic group, this scoping review sought to examine the extent to which nutritional interventions incorporated culturally relevant topics into their design and analyses. Methods. A literature search of 5 databases was conducted for any peer-reviewed studies on nutritional and culinary medicine interventions published between 2000 and 2019. Results. Studies were divided into 2 categories, medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Similar to other dietary intervention studies found in our review of existing literature ( 23 , 24 , 28 ), culturally-focused culinary medicine studies have predominantly been conducted in Hispanic/Latinx populations and in populations with diabetes (75%) ( 30 , 37 ). Despite its importance, studies have highlighted a gap in culinary medicine interventions focused on Asian populations–despite recognition of this population’s increased cardiovascular disease risks ( 37 ). Despite this lack of literature, a nascent culinary medicine movement is seen to be rising in popularity within the Filipino community, with an established group of more than 2,000 members predominant on social media ( 38 ).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar to other dietary intervention studies found in our review of existing literature ( 23 , 24 , 28 ), culturally-focused culinary medicine studies have predominantly been conducted in Hispanic/Latinx populations and in populations with diabetes (75%) ( 30 , 37 ). Despite its importance, studies have highlighted a gap in culinary medicine interventions focused on Asian populations–despite recognition of this population’s increased cardiovascular disease risks ( 37 ). Despite this lack of literature, a nascent culinary medicine movement is seen to be rising in popularity within the Filipino community, with an established group of more than 2,000 members predominant on social media ( 38 ).…”
Section: Introductionsupporting
confidence: 67%
“…Studies have found that culinary medicine approaches are low-cost and high-impact ( 33 ), have improved dietary attitudes, culinary skills, and dietary intake, and can increase self-efficacy and competence in nutrition knowledge ( 32 , 34 )–all of which are found to be important for blood pressure control ( 35 , 36 ). While this intervention type has been shown to be successful, studies have also highlighted the need for cultural competency in this setting, with findings of higher diet adherence, improvements in disease management, and lower chronic disease burden when cultural elements are incorporated ( 37 ). Similar to other dietary intervention studies found in our review of existing literature ( 23 , 24 , 28 ), culturally-focused culinary medicine studies have predominantly been conducted in Hispanic/Latinx populations and in populations with diabetes (75%) ( 30 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, chronic disease burden is higher and multimorbidity, defined as having two or more coexisting chronic conditions, starts at an earlier age in Hispanic/Latino and African American populations compared to their white counterparts ( 36 ). Incorporating culture into nutritional counseling may incite greater adherence to dietary changes ( 37 ) and, consequently, promote better health. For example, a recent study showed that a cookbook tailored to a Filipino-American population may potentially motivate individuals to make healthier dietary choices ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…CM interventions have demonstrated a significant pre-to-posttest reduction in hemoglobin A1c levels, diastolic blood pressure, and cholesterol levels in people with T2DM [13,14]. However, there still exists a need to include more culturally relevant topics in the design and implementation of CM interventions for minority populations [15], which the toolkit described in this study seeks to address.…”
Section: Introductionmentioning
confidence: 99%